SISTEM POLITIK TRADISIONAL, SEJARAH INSTITUSI, DAN LEMBAGA POLITIK KABUPATEN BARRU - Andi M. Anwar Zaenong (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
Traditional politic in Barru is a unity which is governed with the confederation/ Passiajingeng in Buginese language. All are cohesive; Datu ri Tanete, Petta ri Berru sibawa Mallusetasi, Arung ri Soppeng Riaja. Hence, intersection of Barru has a monument on display 4 toppings of kingdom closely and the government will be no doubt about the attention of history which makes the existence of diversity in the politic institution in Barru. With the cultural institution as the tradition system, it has the potential to be given facilities based on the decision from the kings at the date of May 29 to 30 2007 in Makassar which suggests the system of cultural politics in each region and province.